HUMAN PAPILLOMA VIRUS AND EPSTEIN-BARR VIRUS IN THE DIAGNOSIS AND CLINICAL COURSE OF CHRONIC HYPERPLASTIC LARYNGITIS - Осипов, Виктор Дмитриевич; Суржикова, Галина Северьевна; Филимонов, Сергей Николаевич; Клочкова-Абельянц, Сатеник Аршавиловна (Medicine in Kuzbass, 2019)
Objective – to study the presence and significance of human papillomavirus and Epstein-Barr virus in the development of chronic hyperplastic laryngitis and evaluate the effectiveness of immunomodulating therapy in the treatment of the disease. Methods. Thirty men with chronic hyperplastic laryngitis aged 30 to 70 years were examined. The comparison group consisted of 30 healthy men over the age of 29 years. The determination of human papillomavirus was carried out by polymerase chain reaction. Antibodies to Epstein-Barr virus antigens were investigated by enzyme immunoassay. Results. Among patients with chronic hyperplastic laryngitis, HPV infection was 50 %: HPV was detected in 15 of the 30 samples studied. At the same time, HPV of type 11 was detected in 3 patients; in 12 cases, human papillomaviruses of high oncogenic risk were detected – genotypes 16, 18, 31, 31. Indirect laryngoscopy revealed diffuse hyperplasia of all sections of the laryngeal mucosa in 9 (30 %) patients with chronic hepatitis C and there was uneven mucosal hyperplasia and its hyperemia in 21 (70 %). Antibodies to capsid and early Epstein-Barr virus antigens were tested in 21 patients with chronic hepatitis C (70 %). Conclusions. The detection of HPV of high oncogenic risk in chronic hepatitis C, the presence of high titers of specific antibodies characterizing the immune response to the Epstein-Barr virus, indicates the activation of the virus in the body of patients with chronic hyperplastic laryngitis. Conducted comprehensive treatment with the inclusion of an inducer of interferon - cycloferon gives a visible clinical effect in the treatment of this category of patients.